Financial Ratio Analysis of PT SOHO GLOBAL HEALTH Tbk's Corporate Performance for 2019-2021 - Novita Syarifah Nur, Novita; Velissa Nadia Suciyanti, Velissa; Febri Anggini, Anggi (Asosiasi Dosen Akuntansi Indonesia, 2023)
Financial ratio analysis is a method of evaluating company performance that uses comparative data contained in financial statements, such as balance sheet statements, income statements, and cash flow statements. Financial ratios provide an overview of a company's financial health, operational efficiency, rate of return on investment, and the company's ability to meet financial obligations. This study aims to analyze the performance of PT Soho Global Health, Tbk from 2019-2021. The object of our research focuses on the 2019-2020 financial reports of PT Soho Global Health.This research uses qualitative methods. This data is used to analyze and develop an analysis of liquidity, solvency, profitability and activity ratios. The data collection technique used is a literature study carried out to enrich knowledge about various concepts that will be used as a basis or guideline in the research process. The data analysis technique used is Descriptive Statistical analysis. The liquidity ratio using the current ratio shows a fairly good performance. The solvency ratio using the debt to asset ratio shows the company's performance in a good situation. The profitability ratio using the net profit margin ratio shows that it is in unfavorable condition. The activity ratio using the ratio of total asset turnover which shows quite good performance.